Effect of sex on muscle-tendon imbalances and tendon micromorphology in adolescent athletes—A longitudinal consideration - Domroes, T.; Weidlich, K.; Bohm, S.; Arampatzis, A.; Mersmann, F. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Imbalances between muscle strength and tendon stiffness may cause high-level tendon strain during maximum effort muscle contractions and lead to tendon structural impairments and an increased risk for tendinopathy in adolescent athletes. However, it remains unclear whether the development of musculotendinous imbalances is influenced by sex. At four measurement time points during a competitive season, we measured quadriceps femoris muscle strength and patellar tendon mechanical properties in 15 female (14.3 ± 0.7 years) and 13 male (16.0 ± 0.6 years) elite handball players of similar maturity using dynamometry and ultrasonography. To estimate the tendon's structural integrity, the peak spatial frequency (PSF) of proximal tendon ultrasound scans was determined. Females demonstrated significantly lower muscle strength (p < 0.001) and patellar tendon stiffness (p < 0.001) than males with no significant changes over time (p > 0.05). Tendon strain during isometric maximum voluntary contractions and PSF neither differed between sexes nor changed significantly over time (p > 0.05). We found lower fluctuations in muscle strength (p < 0.001) in females during the season but no differences in the fluctuations of tendon strain, stiffness, and PSF (p > 0.05). Descriptively, there was a similar frequency (~40%) of athletes with high-level tendon strain (>9%) in both sexes. These findings suggest that the lower strength capacity of female athletes is paralleled by lower tendon stiffness. Thereby, muscle-tendon imbalances occur to a similar extent in both sexes leading to increased strain levels during the season, which indicates the need for specific tendon training.